Pemanfaatan Google Classroom Sebagai Sarana Pembelajaran Kolaboratif di SDN Cilegon 11 - Wahyuddin; Ahmad Kautsar; Sulasno; Denny Kurnia; Deviyantoro (Jurnal PKM Merah Putih, 2025)
This community service activity aims to enhance the digital competency of the teachers at SDN Cilegon 11 through the utilization of Google Classroom as a collaborative learning tool. The program was conducted over two months using a participatory approach based on hands-on practice (learning by doing) and ongoing mentoring. The participants consisted of 12 teachers from various grade levels. The activities were carried out in several stages, starting with a needs analysis to understand the initial conditions and challenges faced by the teachers in managing digital learning. Following this, an intensive training session was held covering various aspects of using Google Classroom, including setting up digital classrooms, creating and managing assignments, and conducting online assessments. After the training, the teachers implemented Google Classroom in their lessons, followed by an evaluation to assess the effectiveness of the platform's use. The results of the activity showed significant improvement in the teachers' ability to manage digital classrooms, create and assign tasks, conduct online assessments, and facilitate collaborative interactions among students. Reflections on the activity also revealed that the use of Google Classroom not only enhanced the effectiveness of learning but also fostered a collaborative work culture and improved digital literacy within the primary school environment. Full support from the school principal and good collaboration among the teachers were key factors in the success of this program. In the future, similar activities are expected to be expanded to other schools in the Cilegon area.